3D forward stratigraphic modeling of the Albian succession in a part of the northeastern margin of the Arabian Plate and its implications for exploration of subtle traps. (November 2022) - Shabani, Faramarz; Amini, Abdolhossein; Tavakoli, Vahid; Honarmand, Javad; Gong, Changrui
Abstract: During the Albian age, siliciclastic input in the Arabian carbonate-dominated shelf formed important petroleum system elements. Hence, the Albian Burgan-Kazhdumi succession hosts world-class sandstone reservoirs in some Middle East oil fields. Moreover, stratigraphic traps are possible due to changes in facies and structural dips. Accordingly, we used process-based forward stratigraphy modeling as a powerful tool to predict Burgan-Kazhdumi units and de-risking new exploration prospects. A 3D stratigraphic model was constructed in this study for the first time by integrating multi-disciplines and multi-scales of seismic and well data from several countries. The model (324 km × 264 km, 4 km × 4 km grid size) encompasses NW of the Persian Gulf, Kuwait, south Iraq and SW of Iran and is vertically divided into three units based on Albian regional third-order sequences. Results indicated that the lower unit, unit-1, contains onlapping aggradational-retrogradational stacking compounds, high sand bodies thickness and distribution as well as good reservoir quality. This unit was deposited on a tide-dominated delta system. Gradually, with rising sea level, progradational fine-grain marine sedimentation dominated in units 2 and 3. Hence, intra-formational seal facies formed in the proximal and organic-rich facies in the distal intra-shelf areas. The gentle topography of the basin floor seems responsible for the lack of turbidity lobes. The sand bodies of up-dip arches such as Khafji-Norooz and Kharg-Mish highs and pinched out in fine-grained facies provide a significant potential for stratigraphic traps. The model sensitivity analysis showed eustasy, and water-driven diffusion coefficient (Kw) has the most critical impact on the clastic sedimentation of unit-1 and unit-3. Furthermore, tectonic events have the most significant sedimentation effect in unit-2 sedimentation. The findings of this study can help for better understanding of a more precise regional sequence stratigraphic and stratigraphic architecture of the Albian succession of the study area. This study also helps identify elements of petroleum plays as well as stratigraphic trap potential between mixed siliciclastic-carbonate depositional systems. Highlights: Construction of paleo-environment characteristics of the Albian Burgan-Kazhdumi succession in the northeastern margin of the Arabian Plate. Application of multi-disciplinary process-based forward stratigraphy modeling technique for the exploration of subtle traps. Determination of mixed siliciclastic-carbonate lithotype and thickness of Albian Burgan-Kazhdumi succession in the ∼90, 000 km 2 for the first time.